Neuronal Adenosine A1 Receptor is Critical for Olfactory Function but Unable to Attenuate Olfactory Dysfunction in Neuroinflammation - Schubert, Charlotte; Schulz, Kristina; Träger, Simone; Plath, Anna-Lena; Omriouate, Asina; Rosenkranz, Sina C.; Morellini, Fabio; Friese, Manuel A.; Hirnet, Daniela (Frontiers in Cellular Neuroscience, 2022)
Adenine nucleotides such as ATP, ADP, and adenosine are important modulators of neuronal function by engaging P1 and P2 purinergic receptors. In mitral cells, signaling of the G protein-coupled P1 receptor adenosine 1 receptor (A1R) affects the olfactory sensory pathway by regulating high voltage-activated calcium channels and two-pore domain potassium channels. Central nervous system (CNS) inflammation impairs olfactory function and gives rise to large amounts of extracellular ATP and adenosine, which act as pro-inflammatory and anti-inflammatory mediators, respectively. However, it is unclear whether neuronal A1R in the olfactory bulb modulates sensory function and how this is impacted by inflammation. Here we show that signaling via neuronal A1R is important for physiological olfactory function, while it cannot counteract inflammation-induced hyperexcitability and olfactory deficit. Using neuron-specific A1R-deficient mice in patch-clamp recordings, we found that adenosine modulates spontaneous dendro-dendritic signaling in mitral and granule cells via A1R. Furthermore, neuronal A1R deficiency resulted in olfactory dysfunction in two separate olfactory tests. In mice with experimental autoimmune encephalomyelitis (EAE) we detected immune cell infiltration and microglia activation in the olfactory bulb as well as hyperexcitability of mitral cells and olfactory dysfunction. However, neuron-specific A1R activity was unable to attenuate glutamate excitotoxicity in primary olfactory bulb neurons in vitro or EAE-induced olfactory dysfunction and disease severity in vivo. Together, we demonstrate that A1R modulates the dendro-dendritic inhibition at the site of mitral and granule cells and impacts the processing of the olfactory sensory information, while A1R activity was unable to counteract inflammation-induced hyperexcitability.